2011
DOI: 10.1002/hyp.8138
|View full text |Cite
|
Sign up to set email alerts
|

Assessing impacts of agricultural water interventions in the Kothapally watershed, Southern India

Abstract: The paper describes a hydrological model for agricultural water intervention in a community watershed at Kothapally in India, developed through integrated management and a consortium approach. The impacts of various soil and water management interventions in the watershed are compared to no-intervention during a 30-year simulation period by application of the calibrated and validated ARCSWAT 2005 (Version 2.1.4a) modelling tool. Kothapally receives on average 800 mm rainfall in the monsoon period. 72 per cent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 40 publications
3
93
0
Order By: Relevance
“…The challenge is to deliver WSD in a way that is technically and economically effective, whilst taking into account of the water requirements of downstream areas. Garg et al (2011b) reports that in the Kothapally micro-watershed of the Musi sub-Basin, the surface water outflow was reduced by more than 50 % after the implementation of the watershed development programme. When such treatments are applied in a widespread fashion, Garg et al (2011b) demonstrated that this has significant implications on downstream flows to the Osman Sagar reservoir that provides supply to Hyderabad (the sixth biggest city in India).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge is to deliver WSD in a way that is technically and economically effective, whilst taking into account of the water requirements of downstream areas. Garg et al (2011b) reports that in the Kothapally micro-watershed of the Musi sub-Basin, the surface water outflow was reduced by more than 50 % after the implementation of the watershed development programme. When such treatments are applied in a widespread fashion, Garg et al (2011b) demonstrated that this has significant implications on downstream flows to the Osman Sagar reservoir that provides supply to Hyderabad (the sixth biggest city in India).…”
Section: Discussionmentioning
confidence: 99%
“…Major WSD programs are undertaken to counter groundwater over-exploitation (as well as soil erosion) across the drier rainfed areas of India, including within the Upper Bhima (Garg et al, 2011b). Modelling the anticipated expansion in WSD first requires an estimate of the sub-basin's excess surface water that is available for harvesting.…”
Section: Groundwater Recharge and Development Projectionsmentioning
confidence: 99%
“…Check dams and water harvesting storage structures play an important role in augmenting water resources at community or village scale. Garg and co-workers 15,16 showed that constructing small and medium water harvesting structures in watershed could harvest 30-60% of runoff water and enhance groundwater recharge in a semi-arid tropical regions. Water harvesting storage capacity developed in a given watershed or landscape could be provided on per hectare basis in WIC.…”
Section: Reservoir Hydrologymentioning
confidence: 99%
“…While rainwater harvesting in watersheds may help in increasing water availability for upstream farmers, in some cases it may hurt the downstream farmers; an assessment in a semi-arid watershed in Andhra Pradesh found that water-flows out of a developed area declined significantly, hurting the downstream users (Garg, Karlberg, Barron, Wani, & Rockstrom, 2011). If water storage systems upstream result in reduced water availability to communities downstream, these communities may have to be compensated by the upstream beneficiaries.…”
Section: Upstream -Downstream Linkagesmentioning
confidence: 99%